(untitled) (Journal of the College of Education for Women, 2019)
Anticyclone of synoptic studies that influence weather and climate of Iraq, The aim ofthe study is to clarify the effect variation of repetition of Anticyclone and effect on thermalcharacteristic in Iraq were pressure level has been analyzed (1000) millibars and that becauseof pressure level is the closet to the earth surface and the clarity of climatic phenomenonbased on a systematic analysis of synoptic seeking maps and observation and (12:00)according to timing GMT for five climatic stations which is (Mosul, Kirkuk, Baghdad, Rutba,and Basra) and so far three consecutive climatic cycles which is first climatic cycle for period(1986-1976). and second climatic cycle for period (1997-1987) and third climatic cycle forperiod (2008-1998).It become clear from the result. That study reach, It become clear that a clear depressionin repetition of Anticyclone from climatic session to another climatic session followed bythree climatic session and on all level of study area stations. The contrast repetition ofAnticyclone is one of the factors that help to raise the temperature due to air stillness and theclarity of the sky that led to the concentration of pollutant and slow in their transition to otherareas. These pollutant increase rising temperatures air textures to the surface of earth becauseit absorb ground radiation at night and reflect it to surface of earth as well as the clarity of thesky during the day helped to increase the amount of solar radiation to the earth it is foundrising temperatures Siberian is the station (Mosul, Kirkuk, Rutba) for October month forsecond climatic cycle for period (1997-1987) and third for period (2008-1998) as well asincrease temperatures maximum rate with increasing repetition rate of high semi-orbital in thestations Mosul, Kirkuk, and Rutba area for each month of January and October in the secondclimatic session for period (1997- 19987) as well as in the third climatic cycle for period(2008-1998) in all stations of studying area for months of January and march and October andthe high rate of maximum temperature with high rate repetition of European Anticyclone inall stations of studying area in the second climatic cycle for period(1997-1987) 0f January,march, October months, Notice increase repetition rate of Siberian Anticyclone in the monthof October for two climatic cycle second and third as well as Basra station recorded increasein minimum temperature rate with increase repetition rate of high semi-orbital in the secondclimatic cycle for period (1997-1987) for January as well as in all stations of studying area inthe third climatic cycle for period (2008-1998) for march also in stations of Mosul, Kirkuk,Basra for two climatic cycle the second and the third for October. And high rate of minimumtemperature with high repetition rate of European Anticyclone in the stations of Kirkuk andBasra in January for the second climatic cycle period (1997-1987) as well as recorded inmarch month in stations of Mosul and Kirkuk, Basra for two climatic cycle the second andthird also in October for the second climatic cycle for stations of studying area.